Electrochemical Water Splitting By Redox Active Metal Organic Frameworks - Sharma, Komal (My University, 2019)
Water splitting has become an important technique in the production of hydrogen that can be used as fuel in various fields. This process requires electrocatalyst with low overpotential and should exhibit best reaction kinetics for HER (Hydrogen Evolution Reaction) and OER (Oxygen Evolution Reaction). In this report we have prepared electrocatalysts with low overpotential for HER and OER. Further XRD, BET studies were done to know the characteristics of prepared catalyst.
M.Sc. Chemistry
Keywords: Water Splitting; OER; HER; MOFs; Tafel Plot